Analysis on field trial of high temperature heat pump integrated with thermal energy storage in domestic retrofit installation. (October 2018) - Shah, Nikhilkumar N.; Wilson, Christopher; Huang, Ming J.; Hewitt, Neil J.
Graphical abstract: Highlights: Presents 1-year field trial outcome of HTHP and TES in domestic retrofit setting. Heat pump average COP of 2.2 in direct mode to provide 75 °C flow temperature. Storage mode- high energy output during first call for heat but low system COP. Combined mode-benefits of combined operation of heat pump and TES at peak times. CO2 emission saving potential of 30% with COP 2.5 compared to gas boiler. Abstract: Heat pump and thermal energy storage are important technologies to decarbonise heat and electricity sector. Heat pump integrated with thermal energy storage can provide flexibility to electrical system operator to shift demand to accommodate non-synchronous generators. However, ageing housing stock and high temperature wet radiator central heating system possess some challenges for heat pump installation in the UK. To understand the challenges of retrofit technologies in the domestic sector, a field trial was carried out with a cascade heat pump integrated with a thermal storage tank. The heat pump replaced an existing gas boiler to provide flow temperature of 75 °C as a retrofit measure without any modification/replacement to existing controller or radiators in the house. The heat pump was integrated with a 600 l thermal store to meet heating demand and system performance was measured in different operation mode such as direct mode, storage mode and combined mode during one-year. The paper provides performance analysis of the system in different mode with operational experience, limitation and issues with the heat pump, house heat loss/insulation and sizing of thermal store in retrofit installation. Additionally, heat pump performance was compared with gas boiler to establish emission and cost saving benefits.